Computer Networks 17th Conference, CN 2010, Ustron, Poland, June 15-19, 2010. Proceedings - Kwiecien, Andrzej; Gaj, Piotr; Stera, Piotr (Communications in Computer and Information Science, 2010)
The continuous and intensive development of computer science results in the fast progress of computer networks. Computer networks, as well as the entire computer science ?eld, are subject to regular changes caused by the general development of technology, and also the in?uence of new computer science te- nology. This progress refers to the methods as well as the tools of designing and modelingcomputernetworks. Particularly,therangeofusingcomputernetworks permanently is extended thanks to the results of new research and new app- cations, which were not even taken into consideration in the past. These new applications stimulate the development of scienti?c research, because the wider use of system solutions based on computer networks results in both theoretical and practical problems. This book is the evidence of the above considerations, with particular chapters referring to the broad spectrum of issues and problems. This book is the result of the research of scientists from many remarkable scienti?c research centers. It was created as a collection of articles presented during the 17th edition of the International Conference 'Computer Networks', which took place in Ustro? (Poland) during June 15-19, 2010. This conference, organized continuously since 1994 by the Institute of Informatics of Silesian University of Technology, is the oldest event of this kind organized in Poland, having an international status for three years. This year's edition like last year, took place under the auspices of IEEE Poland Section.